Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT Citra Graha Selaras Jakarta Barat - Ditya, Nanda; Lahat, Mohammad Amas; Utama, Dani Chandra (CV Warnak Johanna Nusantara, 2025)
This study aims to explain the partial and simultaneous influence of work discipline and work environment variables on employee performance at PT Citra Graha Selaras. This type of research is quantitative research because it is related to numbers and statistics to test variables and hypotheses. Data processing uses the SPSS version 21 program, The population in this study amounted to 37 employees who are employees of PT Citra Graha Selaras. The researcher conducted several tests including multiple linear regression analysis, classical assumption tests, hypothesis tests and determination coefficient tests. The sampling technique used is saturated sampling. The results of the T-test show that work discipline and work environment have a significant effect on employee performance with a significant value of 0.006 <0.05 and the results of the F-test show that the work environment and work discipline have a simultaneous effect on employee performance because the F-count value is 61,388> F-table 3.27